Welding mechanization and automation in shipbuilding worldwide - Boekholt, Richard (Woodhead Publishing series in welding and other joining technologies., 2011)
This report contains information from more than sixty shipyards from around the world, and gives a unique inventory of the different aspects of welding mechanization and automation used in building large, middle and small-sized ships. Shipbuilders, marine engineers and trade organisations will welcome and value this unique collection of data, assembled for the first time in such a comprehensive format, and interpreted by the author into trends for the future operation of the industry.